Histolomorphological patterns in 50 bone marrow aspiration failure cases - Barua, Ashim Ranjan; Rahman, Jalilur; Tariquzzaman, Mustafa; Barua, Dipi (Bangladesh Journal of Pathology, 2010)
DOI: 10.3329/bjpath.v25i1.4127 Bangladesh J Pathol 25(1): 18-22